Isolated unilateral hypoglossal nerve palsy due to schwannoma - (:unkn) unknown (EGE UNIV, 2018)
As benign nerve sheat tumors, schwannomas are located mostly in the head and neck region, but rarely originate from the hypoglossal nerve. A woman aged 53 years presented with non-progressive dysarthria and unilateral tongue atrophy, which she had had for 2 years. Neurologic examination revealed left-sided, isolated hypoglossal nerve palsy. Chronic axonal neuropathy of the left hypoglossal nerve was seen in electromyographic (EMG) study. With cranial magnetic resonance MR) imaging, a mass lesion in the left cerebellomedullary cistern was detected. A biopsy was not possible due to its critical location. Due to the non-progressive clinical course and radiologic features of the mass, it was consiered as schwannoma. Six-monthly follow-up with MR imaging and EMG was performed three times, and there was no change in the findings. We aimed to provide clinical, radiologic and electrophysiologic findings of isolated unilateral hypoglossal nerve palsy due to schwannoma.
Keywords: Hypoglossal nerve; schwannoma; isolated; unilateral; hypoglossal nerve palsy; OF-THE-LITERATURE; NECK SCHWANNOMAS; HEAD